Perspektive in dileme muslimanskih skupnosti - Pašić, Ahmed (Monitor ISH, 2009)
The West-East relationship is burdened by negative images and lessons from the past, which are being transferred into the present through the mass media, the education systems, and the power centres. The dominant discourse on both sides is hampering communication with negative stereotypes from the past, while ignoring centuries of peaceful coexistence and cooperation in science, philosophy, literature, etc. The West and East construe each otherč indeed, the existence of each depends on the existence of the Other. After all, Christianity as the religious and cultural pillar of Western civilisation is actually derived from the Middle East.
Keywords: integracija; islam; Europe; Evropa; manjšine; Muslim; muslimani